Faktor-Faktor yang Berhubungan dengan Perilaku SADARI sebagai Deteksi Dini Kanker Payudara pada Remaja Putri - Arum Ayomi Ningtias; Sulistya Hartono Putri; Asih Swarsih; Retno Anggraeni Puspita Sari; Aprilina Sartika; Tri Wahyuni Ismoyowati (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Breast cancer is a malignant neoplasm of the breast tissue and remains one of the leading health problems among women worldwide. Early detection can be performed through Breast Self-Examination (BSE), which is considered simple, cost-effective, and non-invasive. However, the level of knowledge and practice of BSE among adolescent girls remains low. This study aims to analyze the factors associated with BSE behavior among female students at SMA Nurul Yaqin, Bekasi Regency. A quantitative approach with a cross-sectional design was employed, involving 35 students from grades X–XII selected through total sampling. A structured questionnaire was used to measure knowledge, attitudes, information exposure, family support, and healthcare provider support. The results showed that knowledge (p = 0.003; OR = 13.500), attitude (p = 0.005; OR = 8.250), information exposure (p = 0.027; OR = 6.476), family support (p = 0.008; OR = 10.286), and healthcare provider support (p = 0.046) were significantly associated with BSE behavior, whereas age was not significant (p = 0.565; OR = 2.923). These findings highlight the need to strengthen school- and family-based health education through structured interventions that enhance health literacy, motivation, and social support to encourage consistent early detection practices.